Continuous renal replacement therapy for haemodynamic collapse and rhabdomyolysis induced by pheochromocytoma crisis. (15th August 2016) - Zhou, Xi; Zhao, Chuhuan; Feng, Xiafei; Samanta, Anweshan; Lin, Yi nuo; Chen, Jun; Dai, Xiaochun; Hong, Xia; Xie, Qiangli; Huang, Weijian
Abstract: Pheochromocytoma associated with pregnancy is not common. Caesarean section may induce pheochromocytoma crisis, resulting in a lethal condition. The clinical picture of pheochromocytoma crisis is extremely variable. In this report, we describe a case of severe pheochromocytoma crisis induced by caesarean section presenting with hyperpyrexia, haemodynamic collapse, muscle weakness, heart failure, and acute kidney injury. Furthermore, we report that the muscle weakness was a manifestation of rhabdomyolysis, resulting from the pheochromocytoma crisis. Standard medical therapy failed to halt the patient's rapidly deteriorating condition. Continuous renal replacement therapy removed catecholamines from the circulation, resulting in improvement of haemodynamics and abrogation of rhabdomyolysis.